1982
DOI: 10.1029/rs017i005p00913
|View full text |Cite
|
Sign up to set email alerts
|

A review of theories of coherent radio wave propagation through precipitation media of randomly oriented scatterers, and the role of multiple scattering

Abstract: In most practical problems involving radio wave transmission through precipitation, the average, or coherent, field is one of the most important quantities. Although the classical formulation describing coherent propagation effects such as attenuation has existed for many years, it is only recently that this formulation has been extended to adequately include polarization effects. In the last 10 years, a number of theories that take into account the polarization effects caused by the random orientations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A well known approach is the one described by the integral equation of Twerskii-Foldy for the coherent field [31]. Supposing a low particle density and a negligible particle size so that the location and the characteristics of each scatterers are independent of the location and characteristics of other scatterers (thus simplifying the statistical averaging), it can be shown that behaves locally as a plane wave and satisfies the Helmholtz homogeneous equation , where the effective (complex) propagation constant is given by [23], [30] (1)…”
Section: A Theoretical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A well known approach is the one described by the integral equation of Twerskii-Foldy for the coherent field [31]. Supposing a low particle density and a negligible particle size so that the location and the characteristics of each scatterers are independent of the location and characteristics of other scatterers (thus simplifying the statistical averaging), it can be shown that behaves locally as a plane wave and satisfies the Helmholtz homogeneous equation , where the effective (complex) propagation constant is given by [23], [30] (1)…”
Section: A Theoretical Considerationsmentioning
confidence: 99%
“…Excellent review works describe these efforts [17], [23], [24], [27]. A well known approach is the one described by the integral equation of Twerskii-Foldy for the coherent field [31].…”
Section: A Theoretical Considerationsmentioning
confidence: 99%
“…Once these parameters have been determined for a rain scatter volume, the transmission matrix T of the rain volume can be calculated for other frequencies and directions of incidence of a plane wave. The transmission matrix of rain volumes has been calculated using the coherent forward multiple scattering approximation described in [6].…”
Section: Polarimetric Radar Measurements In Rainmentioning
confidence: 99%
“…3) The above propagation constants can be expressed as (1) (2) where is the free-space propagation constant, and expressions for and as functions of the microphysical characteristics of the rain medium have been provided by different authors [2], [13]. With these premises, fields at points B and C, separated by distance , can be related as follows:…”
Section: Propagation Effects On Scattering and Covariance Matrix mentioning
confidence: 99%
“…Modeling and analysis of rain effects on coherent wave propagation have been addressed by different authors. Of particular interest is the review and comparison of the different coherent models developed by Olsen [2], where attention is focused on the similarities and differences between several general formulations for precipitation media with random scatterer orientations, and the implications of realizing different assumptions and considerations about the microphysical properties of the medium (distribution of sizes, orientations, etc.) on the expressions for the propagation constants.…”
Section: Introductionmentioning
confidence: 99%